Therapeutic strategies with oral fluoropyrimidine anticancer agent, S-1 against oral cancer() - Harada, Koji (Jpn Dent Sci Rev, 2017)
Oral cancer has been recognized as a tumor with low sensitivity to anticancer agents. However, introduction of S-1, an oral cancer agent is improving treatment outcome for patients with oral cancer. In addition, S-1, as a main drug for oral cancer treatment in Japan can be easily available for outpatients. In fact, S-1 exerts high therapeutic effects with acceptable side effects. Moreover, combined chemotherapy with S-1 shows higher efficacy than S-1 alone, and combined chemo-radiotherapy with S-1 exerts remarkable therapeutic effects. Furthermore, we should consider the combined therapy of S-1 and molecular targeting agents right now as these combinations were reportedly useful for oral cancer treatment. Here, we describe our findings related to S-1 that were obtained experimentally and clinically, and favorable therapeutic strategies with S-1 against oral cancer with bibliographic considerations.